2016
DOI: 10.1515/bmc-2016-0012
|View full text |Cite
|
Sign up to set email alerts
|

Can irisin be a linker between physical activity and brain function?

Abstract: Irisin was initially discovered as a novel hormone-like myokine released from skeletal muscle during exercise to improve obesity and glucose dysfunction by stimulating the browning of white adipose tissue. Emerging evidence have indicated that irisin also affects brain function. FNDC5 mRNA and FNDC5/irisin immunoreactivity are present in various regions of the brain. Central irisin is involved in the regulation of neural differentiation and proliferation, neurobehavior, energy expenditure and cardiac function.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 42 publications
(62 reference statements)
0
27
0
Order By: Relevance
“…Moreover, since the motor system extends beyond the brain, further work will be needed to show that the cognitive reserve does not derive from the effects of physical activity in other key motor regions outside the brain. 45,46 Finally, the activity monitors used in this study do not differentiate between different physical activities, so further studies are necessary to determine whether the cognitive reserve provided by physical activity derives from any increases in movement or whether particular types of activity drive this reserve, i.e., steps vs arm movements, and removal of the device cannot always be distinguished from periods of no activity.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, since the motor system extends beyond the brain, further work will be needed to show that the cognitive reserve does not derive from the effects of physical activity in other key motor regions outside the brain. 45,46 Finally, the activity monitors used in this study do not differentiate between different physical activities, so further studies are necessary to determine whether the cognitive reserve provided by physical activity derives from any increases in movement or whether particular types of activity drive this reserve, i.e., steps vs arm movements, and removal of the device cannot always be distinguished from periods of no activity.…”
Section: Discussionmentioning
confidence: 99%
“…The vital role of Fndc5 in the process of neural differentiation and protection have been shown in many studies [7][8][9][10][11][12][13][14][15]. Fndc5 expression elevates after retinoic acid (RA) treatment of mouse embryonic stem cells (mESCs) in the process of neural differentiation [7].…”
Section: Fndc5 Plays a Vital Role In Neural Differentiation Through Ementioning
confidence: 99%
“…Irisin has been evaluated in young adults and it has been reported that as this hormone increases, there is an elevation in BDNF expression and activation of genes involved in learning and memory [24,25]. Evidence demonstrates that irisin effects brain function [26]. Increased peripheral irisin levels stimulate the hippocampal genes related to neuroprotection, learning and memory [26].…”
Section: Discussionmentioning
confidence: 99%
“…Evidence demonstrates that irisin effects brain function [26]. Increased peripheral irisin levels stimulate the hippocampal genes related to neuroprotection, learning and memory [26]. Telomeres are important DNA protein complexes that are located at chromosome tips to protect genes.…”
Section: Discussionmentioning
confidence: 99%